Dynamics of Heaving Buoy Wave Energy Converters with a Stiffness Reactive Controller - Ahmed H. Sakr; Sayed M. Metwalli; Yasser H. Anis (Energies, 2020)
Heaving buoy wave energy converters (WEC) are floating oscillators, commonly modeled as single-degree-of-freedom vibrating systems. As the wave frequencies change according to the sea state, these devices must be controlled to maximize energy absorption. A new short-term reactive loading control technique is proposed that maximizes power absorption. The control is realized through tuning the effective stiffness of the vibrating system; thus, adjusting its natural frequency to meet the incident waves energy frequency achieving near-to-resonance operation and maximum power absorption. This stiffness is adjusted using an external stiffness, whose value is varied by a continuously variable transmission (CVT) mechanism connected to the buoy. The system equations were derived then solved analytically to calculate the controller bandwidth. Experiments demonstrated promising results for near-resonance tuning at different input frequencies. Results show that an optimized damping value exists at which power absorption can be significantly increased. The WEC equipped with the proposed reactive controller can provide faster tuning actions than long-term techniques. It also works on longer time intervals than phase-control methods; hence, reducing the continuous demands from the PTO system.